Effect of Gold Electronic State on the Catalytic Performance of Nano Gold Catalysts in n-Octanol Oxidation; Nanomaterials; Vol. 10, iss. 5 - Pakrieva E. G. Ekaterina Germanovna; Kolobova E. N. Ekaterina Nikolaevna; Kotolevich Yu. Yulia; Pascual L. Laura; Carabineiro S. A. C. Sonia Alexandra Correia; Kharlanov A. N. Andrey; Pichugina D. Daria; German D. Yu. Dmitry Yuryevich; Partida T. Z. Trino Zepeda; Vazquez H. J. T. Hugo J. Tiznado; Farias M. H. Mario; Bogdanchikova N. Nina; et al. (2020, 2020)
Title screen